Reception power quantization–based emergency message vehicle-to-vehicle multihop broadcast transmission scheme for vehicle accident prevention - Taejun Lee; Jong-Moon Chung (International Journal of Distributed Sensor Networks)
In this article, an emergency message reception power quantization–based time-slot broadcast scheme is proposed for vehicle-to-vehicle multihop communications. The power quantization–based time-slot broadcast scheme derives the optimal reception power quantization size such that time-slot assignments can be made to minimize the average time delay to support quick multihop emergency message broadcasting. The mathematical and simulation performance analysis demonstrates that the proposed power quantization–based time-slot broadcast protocol can reduce the average time delay when compared to the infrastructure-less framework, binary-partition-assisted broadcast, and the trinary-partitioned black-burst-based broadcast schemes.